Synthesis and Reaction of the First 1, 2‐Oxaphosphetane Complexes1. Issue 40 (27th August 2014) - Kyri, Andreas Wolfgang; Nesterov, Vitaly; Schnakenburg, Gregor; Streubel, Rainer
Abstract While PV 1, 2‐oxaphosphetanes are well known from the Wittig reaction, their PIII analogues are still unexplored. Herein, the synthesis and reactions of the first 1, 2‐oxaphosphetane complexes are presented, which were achieved by reaction of the phosphinidenoid complex [Li(12‐crown‐4)(solv)][(OC)5W(Me3Si)2HCPCl] with different epoxides. The title compounds appeared to be stable in toluene up to 100 °C, before unselective decomposition started. Acid‐induced ring expansion with benzonitrile resulted in selective formation of the first complex bearing a 1, 3, 4‐oxazaphosphacyclohex‐2‐ene ligand.